Roṅ-ston Śes-bya-kun-rig's study of the Abhisamayālaṅkāra : being the text of Śes bya pha rol tu phyin paʼi man ṅag gi bstan bcos mṅon par rtogs paʼi rgyan ces bya baʼi rnam bśad tshig don rab tu gsal ba - Roṅ-ston Śes-bya-kun-rig, 1367-1449 (Ngawang Topgay, 1972)
Buddhist Prajnaparamita philosophy; exegetic work by the founder of the Nalendrapa subsect of the Sakyapa tradition.